That old cape magic - Russo, Richard, 1949- (Alfred A. Knopf, 2009)
The lives of Jack and Joy Griffin always seem to come back to Cape Cod, where they honeymooned, as they experience the ups and downs of life, including the deaths of Jack's parents, the marriage of their daughter, and Jack and Joy's divorce.